Modelling cyclists' comfort zones from obstacle avoidance manoeuvres. (September 2020) - Lee, Oliver; Rasch, Alexander; Schwab, Arend L.; Dozza, Marco
Highlights: We modelled cyclist comfortable braking and steering using field experimental data. Cyclists braked with constant deceleration and steered at constant distance. The higher the speed, the more steering came after braking. We exemplify how the models can inform active safety and infrastructure design. Abstract: This paper introduces a framework for modelling the cyclist's comfort zone. Unlike the driver's comfort zone, little is known about the cyclist's. The framework draws on existing literature in cognitive science about driver behaviour to explain experimental results from cycling field trials, and the modelling of these results. We modelled braking and steering manoeuvres from field data of cyclists' obstacle avoidance within their comfort zone. Results show that when cyclists avoided obstacles by braking, they kept a constant deceleration; as speed increased, they started to brake earlier, farther from the obstacle, maintaining an almost constant time to collision. When cyclists avoided obstacles by steering, they maintained a constant distance from the object, independent of speed. Overall, the higher the speed, the more the steering manoeuvres were temporally delayed compared to braking manoeuvres. We discuss these results and other similarities between cyclist and driver behaviour during obstacle avoidance. Implications for the design of acceptable active safety and infrastructure design are also addressed.